PENGARUH PENGURANGAN PENAMPANG TERHADAP KERUSAKAN RANGKA BAJA - Hajar Dwianandha Octariasari; Winda Tri Wahyuningtyas; M. Farid Ma’ruf (JURNAL SPEKTRAN, 2017)
Truss frames are often applied with bridges. Bridges are structures that require early handling to find out the damage and ensure that the bridge is safe. The damage to the bridge element will affect the overall behavior of the bridge. Common cause of bridge damage is reduction of cross section (due to corrosion) and material quality decrease. Damage that occurs need monitoring to avoid the occurrence of structural failure, monitoring is needed. The analysis with program to model the reduction of cross-section by 5%, 10%, 15% and 20%. Truss frames are modeled with a load of P = 3kg. The damage model is limited by 8 cases for section reduction. The reduction of the cross section will result in a decrease in the stiffness of the structure, resulting in changes in displacement values ??and shear forces occurring. The displacement increased by 3% -5% when a reduction was made to the cross section. Join 4 (the middle of the span) has the greatest damage value when compared to other joints of -0.000003489 m, at number 1,7 displacement value is 0 m. In various scenarios the greatest damage is due to the reduction of C rod where the displacement and force increases significance. When the C rod is damaged shear force is increases 6%. The rod that experiences the largest shear force of the D rod (right side C) is then followed by the rods of the support area and the rod that is damaged itself. Keywords: truss frame damage, displacement, cross section reduction, shear force